2013
DOI: 10.1371/journal.pone.0079467
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-324-3p Induces Promoter-Mediated Expression of RelA Gene

Abstract: MicroRNAs (miRNAs) are known to repress translation by binding to the 3’UTRs of mRNAs. Using bioinformatics, we recently reported that several miRNAs also have target sites in DNA particularly in the promoters of the protein-coding genes. To understand the functional significance of this phenomenon, we tested the effects of miR-324-3p binding to RelA promoter. In PC12 cells, co-transfection with premiR-324-3p induced a RelA promoter plasmid in a dose-dependent manner and this effect was lost when the miR-324-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 25 publications
4
74
0
1
Order By: Relevance
“…Macconi et al (35) indicated that miR-324-3p promotes renal fibrosis by targeting prolyl endopeptidase. In addition, a previous study revealed that miR-324-3p targets the promoter of RelA, commonly known as p65, a subunit of nuclear factor-kB, and significantly induced the endogenous RelA mRNA and protein expression in PC12 cells (36). The present results also demonstrated that miR-324-3p exhibited a 48.7-fold increase in the plasma of patients with HCC compared with the control, which may be considered as a biomarker in HCC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Macconi et al (35) indicated that miR-324-3p promotes renal fibrosis by targeting prolyl endopeptidase. In addition, a previous study revealed that miR-324-3p targets the promoter of RelA, commonly known as p65, a subunit of nuclear factor-kB, and significantly induced the endogenous RelA mRNA and protein expression in PC12 cells (36). The present results also demonstrated that miR-324-3p exhibited a 48.7-fold increase in the plasma of patients with HCC compared with the control, which may be considered as a biomarker in HCC.…”
Section: Discussionsupporting
confidence: 76%
“…The remaining 11 miRNAs have never been studied in liver cancer (Table III). Among the 11 differentially dysregulated miRNAs, the function of miR-374a, miR-188-5p, miR-1183, miR-454, miR-324-3p, miR-484, miR-3188, and miR-216b have been studied in human cancers (27,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43); however, the exact function of miR-4271, miR-1471 and miR-3610 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This gene activation mechanism has been termed RNAa [3,4]. RNAa can be triggered by both artificially designed small activating RNAs (saRNAs) and endogenous small RNAs that target gene regulatory sequences or coding regions [2][3][4][5][6][7][8]. RNAa appears to be conserved in evolution, being present in animals ranging from Caenorhabditis elegans (C. elegans) to human [1,2,5].…”
mentioning
confidence: 99%
“…This model is supported by studies that have found miRNAs, mRNA targets, and components of RISC associated with P bodies (24,69). In addition, there have been several examples where miRNAs can positively regulate gene transcription (20,37,59,70,94). This process, referred to as RNA activation, requires complementarity between small double-stranded RNAs and noncoding sequences within the promoters of target genes and involves epigenetic mechanisms (39,55,56).…”
Section: Metabolic Syndrome and Lipoprotein Deregulationmentioning
confidence: 84%